Development of silicon planar P-I-N photodiode - N V Visvanathan, P Susthitha Menon; Shaari, Sahbudin (Penerbit Universiti Sains Malaysia, 2004)
Optical receivers are used to detect optical power and to extract the information that is being transmitted. The incident optical power is detected by a photo detector, usually a PIN or avalanche photodiode (APD). A PIN or APD is an amplitude modulation envelope photo detector, insensitive to phase or small changes in wavelength. It generates an electrical output that reproduces the envelope of the received optical signal (Li, 2000). The most widely deployed photodiode for all lightwave applications is the PIN photodiode where its performance and characteristics are well understood and documented (Campbell, 1995).